A simple deterministic Lorenz chaotic-based methodology to cipher and decipher information - Suárez Castañón, M. S. (2002)
We present in this paper a secure deterministic cipher and decipher mechanism based on the well known Lorenz's dynamic system. The cipher process is performed by the combination of the message to be cipher and the states of the Lorenz's dynamic system, which act as the cipher key. The decipher process is carried out by the reconstruction of the key, which is generated using a Lorenz's system state observer. The observed key is then used in the decipher process in order to recover the ciphered message.